Evaluating Sport Psychology Service Delivery for Elite USA Track and Field Athletes: Findings and Recommendations - Waite, L.; Stanley, C.; Zuleger, B.; Shadle, A. (The Sport Psychologist, 2022)
In preparation for the 2020-2024 Olympic cycle, members of the USA Track and Field sport psychology (SP) subcommittee investigated the SP service provision needs and preferences of 88 elite Olympic-level athletes. A mixed-methods needs analysis was employed, which consisted of surveys, interviews, and a focus group, to help understand current SP usage and shape future SP services for USA Track and Field. Findings highlighted a lack of knowledge and exposure to SP services and a desire for increased contact with SP professionals among athletes, exposing gaps and room for improvement in service delivery. Athletes cited flexibility in terms of service delivery mode and shared common core preferences for mental training, including help managing stress, pressure, emotions, and other challenges of competition and training. The results are discussed in relation to strengthening the effectiveness of service provision through increasing visibility, accessibility, and education regarding the benefits of SP services.